Kontribusi Self Efficacy terhadap Hasil Belajar al- Qur’an Hadist Kelas VIII MTsN 4 Padang Pariaman - Serly Herdella; Iswantir Iswantir (Lembaga Yasin AlSys, 2026)
Self-efficacy has received attention in various educational studies because it is believed to play a role in increasing students’ motivation, persistence, and academic achievement. However, studies that specifically discuss the contribution of self-efficacy to Al-Qur’an Hadith learning outcomes at the madrasah tsanawiyah level remain relatively limited, particularly in the context of MTsN 4 Padang Pariaman. This study aims to analyze the contribution of self-efficacy to the Al-Qur’an Hadith learning outcomes of Grade VIII students at MTsN 4 Padang Pariaman. This study used a quantitative approach with a correlational design. The research participants consisted of 50 students selected using purposive sampling. Data were collected using a self-efficacy questionnaire and documentation of Al-Qur’an Hadith learning outcome scores, then analyzed through descriptive statistics, normality testing, homogeneity testing, linearity testing, Pearson Product Moment correlation testing, partial testing or t-test, and coefficient of determination testing with the assistance of SPSS version 26. The results showed that students’ self-efficacy level was in the high category and their Al-Qur’an Hadith learning outcomes were in the good category. However, the hypothesis testing results showed that self-efficacy did not contribute significantly to Al-Qur’an Hadith learning outcomes, with a significance value of 0.406 (> 0.05), a correlation coefficient of 0.120, and a coefficient of determination of 0.014. These findings indicate that Al-Qur’an Hadith learning outcomes are influenced not only by self-efficacy but also by other factors that were not analyzed in this study. The conclusion of this study affirms that self-efficacy has not become a main predictor of Al-Qur’an Hadith learning outcomes in the context of this study. The implications of this study contribute to the development of Islamic educational psychology studies and serve as input for madrasahs in designing more comprehensive learning strategies to improve students’ learning outcomes.